Minilaparatomy is avoidable during laparoscopic sigmoid vaginoplasty: first experience - S. Paskauskas; T. Latkauskas; R. Augustis; Z. Dambrauskas; A. Bartusevicius; A. Gaurilcikas; J. Celiesiute; D. Vaitkiene; E. Svedas; M. Gedgaudaite; A. Sukovas; R.J. Nadisauskiene (Clinical and Experimental Obstetrics & Gynecology, 2020)
Laparoscopic sigmoid vaginoplasty is a minimally invasive procedure performed in selected Mayer-Rokitansky-Kuster-Hauser syndrome patients and in other conditions when creation of a vagina is indicated. Creation of a colorectal anastomosis is one of the Laparoscopic sigmoid vaginoplasty steps. The biggest disadvantage of it is the enlargement of the portal incision resulting in minilaparotomy to retract the descending colon through the abdominal wall which could lead to postoperative complications. In this report we present a novel perineal approach technique to retract the descending colon for the suture of an anvil in Laparoscopic sigmoid vaginoplasty. Unnecessary enlargement of the port incision or minilaparatomy can be avoided if using this particular technique. A perineal approach technique can be one of the options in Laparoscopic sigmoid vaginoplasty. However, larger numbers of cases are necessary to confirm its benefits.